Revisiting Threshold Fouling Models for Crude Oil Fouling - Deshannavar, U.B. (Taylor and Francis Ltd., 2021)
Threshold crude oil fouling models use activation energy in the deposition rate term to predict the initial fouling rates. It has been reported in the literature that fluid velocity has a strong influence on activation energy, which does not agree well with the principles of chemical reaction engineering. Besides, the existing threshold fouling models always predict an increase in the fouling rate with an increase in film temperature. Several studies reported in the literature reveal that many test crude oils exhibited a decrease in fouling rate with an increase in film temperature caused by an increase in bulk temperature. It is, therefore, necessary to develop a threshold fouling model that is free from the use of activation energy in the model, and that predicts the initial fouling rates correctly for all types of crude oils and fouling mechanisms. In the present study, a modified threshold fouling model has been proposed by introducing a bulk temperature-dependent constant in the place of activation energy and validated with experimental data from our laboratory and data from the literature. Â© 2020 Taylor & Francis Group, LLC.